La promotion de l’environnement à La Réunion : pratiques associatives et enjeux politiques autour d’un gisement d’emplois - Nicolas Roinsard (Développement Durable et Territoires)
To cope with the characteristic mass unemployement of the Reunion Island’s economy, a dual policy promoting both environment and social economy was launched in the nineties by the local councils. This policy was operated on a large scale by the Reunion associations that have grown in great numbers within a few years time. Analysing these structures tends therefore to show that an entire section of the environmental field in Reunion Island comes under, saying the least, the government-driven unemployement measures rather than an environmental policy. As a key notion to the foundations of the social economy, state-approved utility sways, in this case, between the actual guarantee of social peace and the future guarantee of a best preserved environment.